Vitamin D status is associated with relapse rate in pediatric-onset multiple sclerosis - Mowry, Ellen M.; Krupp, Lauren B.; Milazzo, Maria; Chabas, Dorothee; Strober, Jonathan B.; Belman, Anita L.; McDonald, Jamie C.; Oksenberg, Jorge R.; Bacchetti, Peter; Waubant, Emmanuelle (Annals of neurology, 2010)
Objective We sought to determine if vitamin D status, a risk factor for multiple sclerosis, is associated with the rate of subsequent clinical relapses in pediatric‐onset multiple sclerosis. Methods This is a retrospective study of patients with pediatric‐onset multiple sclerosis or clinically isolated syndrome who were consecutively recruited into a prospective cohort at their clinical visit at the pediatric multiple sclerosis center of University of California, San Francisco or State University of New York at Stony Brook. Of 171 eligible patients, 134 (78%) with multiple sclerosis/clinically isolated syndrome were included in the cohort; a further 24 were excluded from this analysis due to lack of available serum (n = 7) or lack of follow‐up (n = 17). Serum 25‐hydroxyvitamin D3 levels were measured and were adjusted to reflect a deseasonalized value. The adjusted serum 25‐hydroxyvitamin D3 level was the primary predictor in a multivariate negative binomial regression model in which the main outcome measure was the number of subsequent relapses. Results Among the 110 subjects, the mean unadjusted 25‐hydroxyvitamin D3 level was 22 ± 9ng/ml. After adjustment for age, gender, race, ethnicity, disease duration, disease‐modifying therapy, and length of follow‐up, every 10ng/ml increase in the adjusted 25‐hydroxyvitamin D3 level was associated with a 34% decrease in the rate of subsequent relapses (incidence rate ratio, 0.66; 95% confidence interval, 0.46–0.95; p = 0.024). Interpretation Lower serum 25‐hydroxyvitamin D3 levels are associated with a substantially increased subsequent relapse rate in pediatric‐onset multiple sclerosis or clinically isolated syndrome, providing rationale for a randomized controlled trial of vitamin D supplementation. ANN NEUROL 2010;67:618–624